2020
DOI: 10.1111/jocn.15428
|View full text |Cite
|
Sign up to set email alerts
|

The experience of living with rheumatoid arthritis: A qualitative metasynthesis

Abstract: Rheumatoid arthritis (RA) is an autoimmune inflammatory disease affecting 0.3%-1% of the population (WHO, 2020). It is a degenerative condition involving the musculoskeletal apparatus, in particular joints and surrounding tissues, causing persistent inflammation, swelling and erosion, which eventually leads to the destruction of cartilage and bones. This is also the cause of both acute and chronic pain, which triggers a generalised persistent fatigue and episodes of flare-up, severely affecting patients' abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Physical deterioration and functional losses also affect patients’ health [ 46 ]. Independence was crucial for patients’ health, supported by findings from a previous meta-synthesis indicating that independence was essential in conducting a normal life [ 8 ].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Physical deterioration and functional losses also affect patients’ health [ 46 ]. Independence was crucial for patients’ health, supported by findings from a previous meta-synthesis indicating that independence was essential in conducting a normal life [ 8 ].…”
Section: Discussionmentioning
confidence: 69%
“…Even though effective treatments are accessible, the disease can affect patients’ health in different ways, including physical, social, emotional, and psychological aspects [ 8 ]. Symptoms can lead to an inability to participate in desired activities and fulfil social roles [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present study show that the mean level of the reported empowerment in patients with RA was comparable with earlier presented data for other chronic diseases (eg, diabetes, which also requires high levels of self‐management) (32–34). Patient empowerment is particularly relevant for patients with chronic disease (eg, RA), given that patients are expected to self‐manage the majority of their care (1,26,27,35). This is of importance because empowerment emphasizes the patient’s own internal resources, which can be negatively affected by RA‐related symptoms and by external factors, such as a lack of social support (36).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, patient empowerment–based care and education aim to enhance autonomy and enable patients to identify needs, make informed decisions, solve problems, and master their life situations (3). Commonly reported needs in patients with RA include how to manage pain and impaired physical function that affects their life situation (1,26). In the present study, patients with low empowerment were slightly older, more often women, and reported worse pain‐related factors, physical function, and health‐related quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation